Nanometer array material for electrochemically removing chloride ions in circulating water of coal-fired power plant as well as preparation method and application of nanometer array material
By using the nanoarray material prepared by suspended polymerization-high temperature carbonization-hydrothermal reaction-inkjet printing method in the circulating water of coal-fired power plants, the problem of removal of high concentrations of chloride ions in circulating water is solved, and the efficient and low-cost chloride ion removal effect is achieved, reducing equipment corrosion and water pollution.
Patent Information
- Application Number
- CN202510340383.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
High concentrations of chloride ions in the circulating water of coal-fired power plants lead to equipment corrosion and water pollution. The existing technology has problems such as low desalination rate, high energy consumption, and expensive equipment investment.
The nanoarray material prepared by suspended polymerization-high temperature carbonization-hydrothermal reaction-inkjet printing method was used to form composite submicron spheres and uniformly disperse on the surface of the sheet-shaped carbonized polyacrylamide submicron particles and composite oxides of TiO2 and CeO2 as chloride ion deletion agents.
It has achieved efficient removal of chloride ions in circulating water of coal-fired power plants, with excellent adsorption, activation and conversion performance, reducing equipment corrosion and water pollution, and has low cost.
Smart Images

Figure CN119838591A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the fields of environmentally friendly materials and water treatment in coal-fired power plants, and in particular to a nanoarray material for electrochemically removing chloride ions from circulating water in coal-fired power plants, and a preparation method and application thereof. Background Art
[0002] The circulating cooling water system is a critical auxiliary system in coal-fired power plants, responsible for removing heat from the generator set condensers and ensuring the normal operation of the units. However, when the circulating water comes into contact with air in the cooling tower, water evaporates, leading to the concentration of salts and a significant increase in the concentration of chloride ions. Chloride ions are highly corrosive ions. High concentrations of chloride ions can damage the passivation film on metal surfaces and accelerate equipment corrosion, especially for equipment made of stainless steel. This can significantly shorten equipment life, increase maintenance costs, and even cause leakage accidents. Furthermore, when the circulating water is discharged, high concentrations of chloride ions can pollute the water environment and harm aquatic life. To ensure the safe and stable operation of the circulating cooling water system, reduce equipment corrosion and scaling, extend equipment life, conserve energy, and protect the environment, the importance of removing chloride ions from the circulating water of coal-fired power plants has become increasingly prominent.
[0003] Currently, the most widely used reverse osmosis method utilizes a semipermeable membrane under pressure to separate water from chloride ions. This method offers advantages such as high salt rejection, ease of operation, and a high degree of automation. However, its high investment cost, along with membrane fouling and high-pressure pump energy consumption, limits its application. Electrodialysis utilizes anion and cation exchange membranes and a direct current electric field to induce directional migration of anions and cations, achieving chloride ion removal. Its low energy consumption, ease of operation, and small equipment footprint make it suitable for removing moderate concentrations of chloride ions. However, its salt rejection rate is inferior to reverse osmosis, and it is susceptible to membrane scaling and polarization. Ion exchange utilizes functional groups on ion exchange resins to exchange with chloride ions. This method is simple to operate and requires low equipment investment, making it suitable for removing low-concentration chloride ions. However, the resin requires regular regeneration, and the wastewater from the regeneration process must be properly disposed of, resulting in a relatively limited processing capacity. Furthermore, chemical precipitation, which involves adding precipitants such as silver nitrate and calcium hydroxide to form an insoluble precipitate, is simple to operate and relatively inexpensive, but its treatment efficiency is low, and the resulting precipitate can easily cause secondary contamination. Although the above methods can treat chloride ions at different concentrations, their shortcomings are also very obvious. Therefore, the development of nano-array materials with high efficiency and low cost for electrochemical removal of chloride ions from circulating water in coal-fired power plants is one of the important development directions for the utilization of circulating water in coal-fired power plants. Summary of the Invention
[0004] The present application aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] In a first aspect, the present application provides a nanoarray material for electrochemically removing chloride ions from circulating water in coal-fired power plants. The nanoarray material comprises surface-modified carbonized polyacrylamide submicron particles as a core, a composite oxide of TiO2 and CeO2 as a chloride ion remover, and carbonized paper as a substrate. The material is prepared by a suspension polymerization-high-temperature carbonization-hydrothermal reaction-inkjet printing method. Based on the mass of the carbonized paper, the mass percentage of the core is 5%-8%, and the mass percentage of the chloride ion remover is 3%-4%. The mass ratio of TiO2 to CeO2 in the chloride ion remover is 1:(0.5-1). Thus, the nanoarray material proposed in this application combines the high conductivity of carbon spheres with the excellent redox properties of titanium-cerium composite oxides. Furthermore, when the oxides grow on the surface of the carbon spheres, they also form nanopores, resulting in excellent adsorption, activation, and conversion properties during direct current electrocatalytic chloride ion removal.
[0006] The second aspect of the present application provides a method for preparing the nanoarray material provided in the first aspect of the present application, the method comprising: S10: Preparation of carbonized polyacrylamide submicron particles Weighing acrylamide and dissolving it in deionized water, adding polyvinyl alcohol and stirring to disperse it to form a slurry, and then heating it in a water bath. After reaching the water bath heating reaction temperature, adding an initiator, continuing to stir until the polymerization reaction is completed, filtering and vacuum drying after the reaction is completed to obtain polyacrylamide powder, and then placing the polyacrylamide powder in a tubular reactor, introducing nitrogen and heating to carbonize it to obtain carbonized polyacrylamide submicron particles, and finally placing the carbonized polyacrylamide submicron particles in a plasma surface treatment instrument, first evacuating the plasma surface treatment instrument, then filling it with oxygen, and then performing surface treatment to obtain surface-modified carbonized polyacrylamide submicron particles; S20: Loaded chloride ion remover A titanium salt is weighed and dissolved in ethanol, and then the surface-modified carbonized polyacrylamide submicron particles are added to obtain a mixed slurry. The mixed slurry is continuously stirred and exposed to air. After the titanium salt is completely hydrolyzed, cerium salt and deionized water are added, and the mixture is placed in a hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, the mixture is filtered and then vacuum dried to obtain a mixed particle powder; S30: Preparation of nanoarray materials The mixed particle powder is weighed and filled into a toner cartridge, and then a paper is placed in an inkjet printer, and the inkjet printer is started to print. After the mixed particle powder is printed on the paper, the printed paper is placed in a tubular reactor, nitrogen is introduced, and the temperature is increased for carbonization, and finally the nanoarray material is obtained.
[0007] The present application proposes a method for preparing a nano-array material, which comprises the following steps: preparing polyacrylamide powder by suspension polymerization of acrylamide and then carbonizing it at high temperature to form carbonized polyacrylamide submicron particles; utilizing the high conductivity of the carbonized polyacrylamide submicron particles to compensate for the insufficient conductivity of the composite oxide, thereby enabling the composite oxide of TiO2 and CeO2 to have excellent electrochemical catalytic removal performance under a weak DC voltage; treating the surface of the carbonized polyacrylamide submicron particles with plasma to increase the concentration of surface hydroxyl groups; finally, utilizing a hydrothermal reaction to convert titanium salt and cerium salt into oxides that grow on the surface of the surface-modified carbonized polyacrylamide submicron particles to form composite submicron spheres; to avoid agglomeration of the composite submicron spheres, which would result in a decrease in electrochemical catalytic performance, the composite submicron spheres are printed on a paper surface by inkjet printing, and then the paper is converted into a flaky carbon material by high-temperature carbonization, ultimately obtaining carbonized polyacrylamide submicron particles coated with the composite oxides of TiO2 and CeO2 uniformly dispersed on the surface of the flaky carbon material, i.e., the nano-array material.
[0008] According to some embodiments of the present application, the initiator includes potassium persulfate or sodium persulfate, and the mass ratio of the acrylamide, the deionized water, the polyvinyl alcohol, and the initiator is 1: (10-20): (0.005-0.010): (0.001-0.005).
[0009] According to some embodiments of the present application, the water bath heating temperature is 50°C-80°C, the water bath heating time is 6h-12h, the vacuum drying temperature is 30°C-60°C, the vacuum degree of the vacuum drying is 0.090MPa-0.095MPa, and the vacuum drying time is 12h-24h.
[0010] According to some embodiments of the present application, the rate of introducing nitrogen is 30 mL / min-60 mL / min, the temperature of heating carbonization is 600° C.-800° C., and the time of heating carbonization is 6 h-12 h.
[0011] According to some embodiments of the present application, the plasma flame scanning rate during the surface treatment is 20 mm / s-40 mm / s, and the volume ratio of the oxygen to the carbonized polyacrylamide submicron particles is 1:(30-60).
[0012] According to some embodiments of the present application, the titanium salt includes tetrabutyl titanate or tetraethyl titanate, the mass ratio of the titanium salt to the ethanol is 1:(30-60), and the stirring rate is 100 r / min-200 r / min.
[0013] According to some embodiments of the present application, the cerium salt includes cerium nitrate hexahydrate or cerium chloride hexahydrate, and the mass ratio of the cerium salt to the deionized water is 1:(60-100).
[0014] According to some embodiments of the present application, the temperature of the hydrothermal reaction is 140°C-160°C, the time of the hydrothermal reaction is 4h-8h, the temperature of the vacuum drying is 30°C-60°C, the vacuum degree of the vacuum drying is 0.090MPa-0.095MPa, and the time of the vacuum drying is 12h-24h.
[0015] The third aspect of the present application provides the use of the nanoarray material provided in the first aspect of the present application in removing chloride ions from circulating water in a coal-fired power plant. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 A schematic flow chart of a method for preparing a nanoarray material according to an embodiment of the present application is shown.
[0017] Figure 2 The FE-SEM image of the nanoarray material prepared in Example 1 of the present application is shown.
[0018] Figure 3 Shows Figure 2 A partial enlarged view of . DETAILED DESCRIPTION
[0019] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this area or according to the product specifications. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0020] In a first aspect, the present application provides a nanoarray material for electrochemically removing chloride ions from circulating water in coal-fired power plants. The nanoarray material comprises surface-modified carbonized polyacrylamide submicron particles as a core, a composite oxide of TiO2 and CeO2 as a chloride ion remover, and carbonized paper as a substrate. The material is prepared by a suspension polymerization-high-temperature carbonization-hydrothermal reaction-inkjet printing method. Based on the mass of the carbonized paper, the mass percentage of the core is 5%-8%, and the mass percentage of the chloride ion remover is 3%-4%, wherein the mass ratio of the TiO2 to the CeO2 in the chloride ion remover is 1:(0.5-1).
[0021] The nanoarray material provided by the present application can achieve efficient removal of chloride ions from circulating water in coal-fired power plants. The nanoarray material is made of polyacrylamide powder prepared by suspension polymerization of acrylamide and then carbonized at high temperature to form carbonized polyacrylamide submicron particles. The high conductivity of the carbonized polyacrylamide submicron particles is used to compensate for the insufficient conductivity of the composite oxide of TiO2 and CeO2, so that the composite oxide of TiO2 and CeO2 can have excellent electrochemical catalytic removal performance under weak DC voltage; in order to enable the composite oxide of TiO2 and CeO2 to grow and coat on the surface of the carbonized polyacrylamide submicron particles to form submicron spheres, the surface of the carbonized polyacrylamide submicron particles is treated with plasma to increase the concentration of hydroxyl groups on its surface; tetrabutyl titanate / tetraethyl titanate is slowly hydrolyzed when it comes into contact with moisture in the air, so that it is evenly grown on the surface-modified carbonized polyacrylamide submicron particles. surface; finally, a hydrothermal reaction is used to convert titanium salt and cerium salt into oxides that grow on the surface of the surface-modified carbonized polyacrylamide submicron particles to form composite submicron spheres; in order to avoid agglomeration of the composite submicron spheres and thus a decrease in electrochemical catalytic performance, they are printed on the surface of paper by inkjet printing, and then the paper is converted into a flaky carbon material by high-temperature carbonization, ultimately obtaining carbonized polyacrylamide submicron particles coated with composite oxides of TiO2 and CeO2 uniformly dispersed on the surface of the flaky carbon material, namely a nanoarray material; the nanoarray material has both the high conductivity of carbon spheres and the excellent redox properties of titanium-cerium composite oxides, and at the same time, nanopores are formed when the oxides grow on the surface of the carbon spheres, so that it has excellent adsorption, activation and conversion properties in the direct current electrocatalytic removal of chloride ions.
[0022] The second aspect of the present application provides a method for preparing the nanoarray material provided in the first aspect of the present application, the method comprising: S10: Preparation of carbonized polyacrylamide submicron particles Weighing acrylamide and dissolving it in deionized water, adding polyvinyl alcohol and stirring to disperse it to form a slurry, and then heating it in a water bath. After reaching the water bath heating reaction temperature, adding an initiator, continuing to stir until the polymerization reaction is completed, filtering and vacuum drying after the reaction is completed to obtain polyacrylamide powder, and then placing the polyacrylamide powder in a tubular reactor, introducing nitrogen and heating to carbonize it to obtain carbonized polyacrylamide submicron particles, and finally placing the carbonized polyacrylamide submicron particles in a plasma surface treatment instrument, first evacuating the plasma surface treatment instrument, then filling it with oxygen, and then performing surface treatment to obtain surface-modified carbonized polyacrylamide submicron particles; S20: Loaded chloride ion remover A titanium salt is weighed and dissolved in ethanol, and then the surface-modified carbonized polyacrylamide submicron particles are added to obtain a mixed slurry. The mixed slurry is continuously stirred and exposed to air. After the titanium salt is completely hydrolyzed, cerium salt and deionized water are added, and the mixture is placed in a hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, the mixture is filtered and then vacuum dried to obtain a mixed particle powder; S30: Preparation of nanoarray materials The mixed particle powder is weighed and filled into a toner cartridge, and then a paper is placed in an inkjet printer, and the inkjet printer is started to print. After the mixed particle powder is printed on the paper, the printed paper is placed in a tubular reactor, nitrogen is introduced, and the temperature is increased for carbonization, and finally the nanoarray material is obtained.
[0023] The present application proposes a method for preparing a nano-array material, which comprises the following steps: preparing polyacrylamide powder by suspension polymerization of acrylamide and then carbonizing it at high temperature to form carbonized polyacrylamide submicron particles; utilizing the high conductivity of the carbonized polyacrylamide submicron particles to compensate for the insufficient conductivity of the composite oxide, thereby enabling the composite oxide of TiO2 and CeO2 to have excellent electrochemical catalytic removal performance under a weak DC voltage; treating the surface of the carbonized polyacrylamide submicron particles with plasma to increase the concentration of surface hydroxyl groups; finally, utilizing a hydrothermal reaction to convert titanium salt and cerium salt into oxides that grow on the surface of the surface-modified carbonized polyacrylamide submicron particles to form composite submicron spheres; to avoid agglomeration of the composite submicron spheres, which would result in a decrease in electrochemical catalytic performance, the composite submicron spheres are printed on a paper surface by inkjet printing, and then the paper is converted into a flaky carbon material by high-temperature carbonization, ultimately obtaining carbonized polyacrylamide submicron particles coated with the composite oxides of TiO2 and CeO2 uniformly dispersed on the surface of the flaky carbon material, i.e., the nano-array material.
[0024] The following is a detailed description of each step of the method, refer to Figure 1 , the method comprising: S10: Preparation of carbonized polyacrylamide submicron particles Acrylamide is weighed and dissolved in deionized water, polyvinyl alcohol is added, stirred and dispersed to form a slurry, and then heated in a water bath. After reaching the water bath heating reaction temperature, an initiator is added, and stirring is continued until the polymerization reaction is completed. After the reaction is completed, the polyacrylamide powder is filtered and vacuum dried to obtain polyacrylamide powder, and then the polyacrylamide powder is placed in a tubular reactor, nitrogen is introduced, and the temperature is increased for carbonization to obtain carbonized polyacrylamide submicron particles. Finally, the carbonized polyacrylamide submicron particles are placed in a plasma surface treatment instrument, the plasma surface treatment instrument is first evacuated, then filled with oxygen, and then surface treatment is performed to obtain surface-modified carbonized polyacrylamide submicron particles.
[0025] According to some embodiments of the present application, the initiator includes potassium persulfate or sodium persulfate, and the mass ratio of the acrylamide, the deionized water, the polyvinyl alcohol, and the initiator is 1: (10-20): (0.005-0.010): (0.001-0.005).
[0026] As an example, the mass ratio of the acrylamide, the deionized water, the polyvinyl alcohol, and the initiator can be 1:10:0.005:0.001, 1:15:0.01:0.003, 1:20:0.01:0.005, etc., or can be a range consisting of any of the above values.
[0027] According to some embodiments of the present application, the molecular weight of the polyacrylamide is 200,000 to 800,000.
[0028] According to some embodiments of the present application, the water bath heating temperature is 50° C.-80° C., and the water bath heating time is 6 h-12 h.
[0029] As an example, the temperature of the water bath heating can be 50° C., 60° C., 70° C., 80° C., etc., or can be a range consisting of any of the above values.
[0030] As an example, the water bath heating time can be 6 h, 8 h, 10 h, 12 h, etc., or can be a range consisting of any of the above values.
[0031] According to some embodiments of the present application, the temperature of the vacuum drying is 30° C.-60° C., the vacuum degree of the vacuum drying is 0.090 MPa-0.095 MPa, and the time of the vacuum drying is 12 h-24 h.
[0032] As an example, the vacuum drying temperature may be 30° C., 40° C., 50° C., 60° C., etc., or may be within a range consisting of any of the above values.
[0033] As an example, the vacuum drying time may be 12 h, 16 h, 20 h, 24 h, etc., or may be within a range consisting of any of the above values.
[0034] According to some embodiments of the present application, the rate of nitrogen introduction is 30 mL / min-60 mL / min. For example, it can be 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, etc., or can be a range consisting of any of the above values.
[0035] According to some embodiments of the present application, the temperature of the carbonization is 600° C.-800° C., and the time of the carbonization is 6 hours-12 hours.
[0036] As an example, the temperature of the carbonization may be 600° C., 650° C., 700° C., 750° C., etc., or may be within a range consisting of any of the above values.
[0037] As an example, the heating and carbonization time may be 6 h, 8 h, 10 h, 12 h, etc., or may be within a range consisting of any of the above values.
[0038] According to some embodiments of the present application, the plasma surface treatment instrument is a Plasma clean-PL-5010 model.
[0039] The voltage of the surface treatment is 220V, and the working distance is 5mm-10mm.
[0040] According to some embodiments of the present application, the plasma flame scanning rate during the surface treatment is 20 mm / s-40 mm / s, for example, 20 mm / s, 30 mm / s, 40 mm / s, etc., or a range consisting of any of the above values.
[0041] According to some embodiments of the present application, the volume ratio of the oxygen to the carbonized polyacrylamide submicron particles is 1:(30-60), for example, 1:30, 1:40, 1:50, 1:60, etc., or any range thereof.
[0042] S20: Loaded chloride ion remover Titanium salt is weighed and dissolved in ethanol, and then the surface-modified carbonized polyacrylamide submicron particles are added to obtain a mixed slurry. The mixed slurry is continuously stirred and exposed to air. After the titanium salt is completely hydrolyzed, cerium salt and deionized water are added, and the mixture is placed in a hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, it is filtered and then vacuum dried to obtain a mixed particle powder.
[0043] According to some embodiments of the present application, the titanium salt includes tetrabutyl titanate or tetraethyl titanate.
[0044] According to some embodiments of the present application, the mass ratio of the titanium salt to the ethanol is 1:(30-60), and the stirring rate is 100 r / min-200 r / min.
[0045] As an example, the mass ratio of the titanium salt to the ethanol can be 1:30, 1:40, 1:50, 1:60, etc., or can be within a range consisting of any of the above values, so that the titanium salt is fully dissolved.
[0046] As an example, the stirring rate may be 100 r / min, 140 r / min, 155 r / min, 180 r / min, 200 r / min, etc., or may be within a range consisting of any of the above values to fully dissolve the titanium salt.
[0047] According to some embodiments of the present application, the cerium salt includes cerium nitrate hexahydrate or cerium chloride hexahydrate, and the mass ratio of the cerium salt to the deionized water is 1:(60-100).
[0048] According to some embodiments of the present application, the temperature of the hydrothermal reaction is 140° C.-160° C., and the time of the hydrothermal reaction is 4 h-8 h.
[0049] As an example, the temperature of the hydrothermal reaction can be 140° C., 145° C., 150° C., 155° C., 160° C., etc., or can be a range consisting of any of the above values.
[0050] As an example, the hydrothermal reaction time can be 4 h, 6 h, 8 h, etc., or can be within a range consisting of any of the above values.
[0051] According to some embodiments of the present application, the temperature of the vacuum drying is 30° C.-60° C., the vacuum degree of the vacuum drying is 0.090 MPa-0.095 MPa, and the time of the vacuum drying is 12 h-24 h.
[0052] As an example, the vacuum drying temperature may be 30° C., 40° C., 50° C., 60° C., etc., or may be within a range consisting of any of the above values.
[0053] As an example, the vacuum drying time may be 12 h, 16 h, 20 h, 24 h, etc., or may be within a range consisting of any of the above values.
[0054] S30: Preparation of nanoarray materials The mixed particle powder is weighed and filled into a toner cartridge, and then a paper is placed in an inkjet printer, and the inkjet printer is started to print. After the mixed particle powder is printed on the paper, the printed paper is placed in a tubular reactor, nitrogen is introduced, and the temperature is increased for carbonization, and finally the nanoarray material is obtained.
[0055] According to some embodiments of the present application, the rate of nitrogen introduction is 30 mL / min-60 mL / min. For example, it can be 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, etc., or can be a range consisting of any of the above values.
[0056] According to some embodiments of the present application, the temperature of the carbonization is 600° C.-800° C., and the time of the carbonization is 6 hours-12 hours.
[0057] As an example, the temperature of the carbonization may be 600° C., 650° C., 700° C., 750° C., etc., or may be within a range consisting of any of the above values.
[0058] As an example, the heating and carbonization time may be 6 h, 8 h, 10 h, 12 h, etc., or may be within a range consisting of any of the above values.
[0059] The third aspect of the present application provides the use of the nanoarray material provided in the first aspect of the present application in removing chloride ions from circulating water in a coal-fired power plant.
[0060] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this area or according to the product specifications. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0061] Example 1 S10: Preparation of carbonized polyacrylamide submicron particles Weigh 100g of acrylamide and dissolve it in 1000g of deionized water. Add 0.5g of polyvinyl alcohol and stir to disperse to form a slurry, then heat it in a water bath at 50℃. After reaching the water bath heating reaction temperature, add 0.1g of potassium persulfate and continue stirring for 12h until the polymerization reaction is completed (maintain the water bath temperature at 50℃ during the stirring process). After the reaction is completed, filter and vacuum dry at 30℃ for 24h (the drying vacuum degree is 0.090MPa) to obtain polyacrylamide powder. Then place the polyacrylamide powder in a tubular reactor and introduce nitrogen (nitrogen rate is 30mL / m in) and heated to 600°C for carbonization for 12 hours to obtain carbonized polyacrylamide submicron particles. Finally, 30 mL of carbonized polyacrylamide submicron particles were measured and placed in a plasma surface treatment instrument. The plasma surface treatment instrument was first evacuated and then filled with 1 mL of oxygen. The carbonized polyacrylamide surface was treated under the conditions of an input voltage of 220 V, a working distance of 5 mm, and a plasma flame scanning rate of 20 mm / s to obtain surface-modified carbonized polyacrylamide submicron particles. The surface modification steps were repeated until the carbonized polyacrylamide particles were used up.
[0062] S20: Loaded chloride ion adsorbent 8.522 g of tetrabutyl titanate was weighed and dissolved in 255.660 g of ethanol, and then 5 g of surface-modified carbonized polyacrylamide submicron particles were added to obtain a mixed slurry. The mixed slurry was continuously stirred at a rate of 100 r / min and exposed to air. After the tetrabutyl titanate was completely hydrolyzed, 2.523 g of cerium nitrate hexahydrate and 151.380 g of deionized water were added, and the mixture was placed in a hydrothermal reactor for hydrothermal reaction at 140° C. for 8 hours. After the hydrothermal reaction was completed, it was filtered and then vacuum dried at 30° C. for 24 hours (the vacuum degree of drying was 0.090 MPa) to obtain a mixed particle powder. Step S20 was repeated until the surface-modified carbonized polyacrylamide submicron particles obtained in step S10 were used up.
[0063] S30: Preparation of nanoarray materials Weigh 50 g of the mixed particle powder obtained in step S20 and fill it into a toner cartridge. Then place a single A4 paper (4.99 g) in an inkjet printer and start the inkjet printer to print. After 0.100 g of the mixed particle powder is evenly printed on the paper, place the printed paper in a tubular reactor, introduce nitrogen (nitrogen rate is 30 mL / min) and heat to 600 ° C for carbonization for 12 h (at this temperature, the ablation residue of the carbonized paper obtained by carbonizing the A4 paper is 25%). Finally, a nanoarray material is obtained. Based on the mass of the carbonized paper substrate, the mass percentage of the core is 5%, and the mass percentage of the chloride ion remover is 3%. Among them, the mass ratio of TiO2 and CeO2 in the chloride ion remover is 1:0.5. The FE-SEM image of the nanoarray material is shown in FIG. Figure 2 and Figure 3 shown.
[0064] Example 2 S10: Preparation of carbonized polyacrylamide submicron particles Weigh 100g of acrylamide and dissolve it in 2000g of deionized water. Add 1g of polyvinyl alcohol and stir to disperse to form a slurry, then heat it in a water bath at 80℃. After reaching the water bath heating reaction temperature, add 0.5g of sodium persulfate and continue stirring for 6h until the polymerization reaction is completed (maintain the water bath temperature at 80℃ during the stirring process). After the reaction is completed, filter and vacuum dry at 60℃ for 12h (the drying vacuum degree is 0.095MPa) to obtain polyacrylamide powder. Then place the polyacrylamide powder in a tubular reactor and introduce nitrogen (nitrogen at a rate of 60mL / min). ) and heated to 800°C for carbonization for 6 hours to obtain carbonized polyacrylamide submicron particles. Finally, 30 mL of carbonized polyacrylamide submicron particles were measured and placed in a plasma surface treatment instrument. The plasma surface treatment instrument was first evacuated and then filled with 0.5 mL of oxygen. The carbonized polyacrylamide surface was treated under the conditions of an input voltage of 220 V, a working distance of 10 mm, and a plasma flame scanning rate of 40 mm / s to obtain surface-modified carbonized polyacrylamide submicron particles. The surface modification steps were repeated until the carbonized polyacrylamide particles were used up.
[0065] S20: Loaded chloride ion remover 3.570 g of tetraethyl titanate was weighed and dissolved in 214.200 g of ethanol, and then 5 g of surface-modified carbonized polyacrylamide submicron particles were added to obtain a mixed slurry. The mixed slurry was continuously stirred at a rate of 200 r / min and exposed to air. After the tetraethyl titanate was completely hydrolyzed, 1.921 g of cerium chloride hexahydrate and 192.100 g of deionized water were added, and the mixture was placed in a hydrothermal reactor for hydrothermal reaction at 160° C. for 4 hours. After the hydrothermal reaction was completed, it was filtered and then vacuum-dried at 60° C. for 12 hours (the drying vacuum degree was 0.095 MPa) to obtain a mixed particle powder. Step S20 was repeated until the surface-modified carbonized polyacrylamide submicron particles obtained in step S10 were used up.
[0066] S30: Preparation of nanoarray materials Weigh 50g of the mixed particle powder obtained in step S20 and fill it into a toner cartridge. Then place a single A4 paper (4.99g) in an inkjet printer and start the inkjet printer to print. After 0.120g of the mixed particle powder is evenly printed on the paper, place the printed paper in a tubular reactor, introduce nitrogen (nitrogen rate is 60mL / min) and heat to 800℃ for carbonization for 6h (the ablation residue of the carbonized paper obtained by carbonization of A4 paper at this temperature is 20%). Finally, a nanoarray material is obtained. Based on the mass of the carbonized paper substrate, the mass percentage of the core is 8%, and the mass percentage of the chloride ion remover is 4%. The mass ratio of TiO2 and CeO2 in the chloride ion remover is 1:1. Performance test The nanoarray material (1 g) was adhered to a stainless steel plate (1 cm × 1 cm) using conductive glue to form a positive electrode, and carbon felt (1 cm × 1 cm) was used as the negative electrode. 100 mL of a 20 mmol / L calcium chloride solution was used as a circulating water simulation solution. After the nanoarray material reacted for 30 minutes at a DC voltage of 4.6 V, the chloride ion concentration in the circulating water was tested. The chloride ion removal rates of Example 1 and Example 2 were 92.6% and 94.8%, respectively.
[0067] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0068] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A nanoarray material for removing chloride ions from circulating water in a coal-fired power plant by electrochemical means, characterized in that: The nanoarray material is prepared by suspension polymerization-high temperature carbonization-hydrothermal reaction-inkjet printing method with surface-modified carbonized polyacrylamide submicron particles as the core, composite oxides of TiO2 and CeO2 as chloride ion removers, and carbonized paper as the substrate; Based on the mass of the carbonized paper, the mass percentage of the inner core is 5%-8%, and the mass percentage of the chloride ion remover is 3%-4%, wherein the mass ratio of the TiO2 to the CeO2 in the chloride ion remover is 1:(0.5-1).
2. A method for preparing the nanoarray material according to claim 1, characterized in that: include: S10: Preparation of carbonized polyacrylamide submicron particles Weigh acrylamide and dissolve it in deionized water, add polyvinyl alcohol, stir and disperse to form a slurry, and then heat it in a water bath. After reaching the water bath heating reaction temperature, add an initiator, continue stirring until the polymerization reaction is completed, filter and vacuum dry after the reaction is completed to obtain polyacrylamide powder, then place the polyacrylamide powder in a tubular reactor, introduce nitrogen and heat it to carbonize it to obtain carbonized polyacrylamide submicron particles, finally place the carbonized polyacrylamide submicron particles in a plasma surface treatment instrument, first evacuate the plasma surface treatment instrument, then fill it with oxygen, and then perform surface treatment to obtain surface-modified carbonized polyacrylamide submicron particles; S20: Loaded chloride ion remover Weigh titanium salt and dissolve it in ethanol, then add the surface-modified carbonized polyacrylamide submicron particles to obtain a mixed slurry, continuously stir the mixed slurry and expose it to air, add cerium salt and deionized water after the titanium salt is completely hydrolyzed, and place it in a hydrothermal reactor for hydrothermal reaction, filter it after the hydrothermal reaction is completed, and then vacuum dry it to obtain a mixed particle powder; S30: Preparation of nanoarray materials The mixed particle powder is weighed and filled into a toner cartridge, and then a paper is placed in an inkjet printer, and the inkjet printer is started for printing. After the mixed particle powder is printed on the paper, the printed paper is placed in a tubular reactor, nitrogen is introduced, and the temperature is increased for carbonization, and finally the nanoarray material is obtained.
3. The method according to claim 2, characterized in that The initiator includes potassium persulfate or sodium persulfate, and the mass ratio of the acrylamide, the deionized water, the polyvinyl alcohol, and the initiator is 1: (10-20): (0.005-0.010): (0.001-0.005).
4. The method according to claim 2, characterized in that: The water bath heating temperature is 50°C-80°C, the water bath heating time is 6h-12h, the vacuum drying temperature is 30°C-60°C, the vacuum degree of the vacuum drying is 0.090MPa-0.095MPa, and the vacuum drying time is 12h-24h.
5. The method according to claim 2, characterized in that: The rate of introducing nitrogen is 30 mL / min-60 mL / min, the temperature of heating carbonization is 600° C.-800° C., and the time of heating carbonization is 6 h-12 h.
6. The method according to claim 2, characterized in that The plasma flame scanning rate during the surface treatment is 20 mm / s-40 mm / s, and the volume ratio of the oxygen to the carbonized polyacrylamide submicron particles is 1:(30-60).
7. The method according to claim 2, characterized in that The titanium salt includes tetrabutyl titanate or tetraethyl titanate, the mass ratio of the titanium salt to the ethanol is 1:(30-60), and the stirring rate is 100r / min-200r / min.
8. The method according to claim 2, characterized in that: The cerium salt includes cerium nitrate hexahydrate or cerium chloride hexahydrate, and the mass ratio of the cerium salt to the deionized water is 1: (60-100).
9. The method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 140°C-160°C, the time of the hydrothermal reaction is 4h-8h, the temperature of the vacuum drying is 30°C-60°C, the vacuum degree of the vacuum drying is 0.090MPa-0.095MPa, and the time of the vacuum drying is 12h-24h.
10. Use of the nanoarray material according to claim 1 in removing chloride ions from circulating water of a coal-fired power plant.
Citation Information
Patent Citations
Novel adsorbent for removing fluorine ions in wastewater and preparation method
CN106830159A
Method for removing chloride ions from reclaimed water and preparation method of electrode
CN111547824A
Carbon fiber composite electrode, preparation method and method for removing chloride ions from raw water
CN116854211A
Cited By
A hydrogel dressing and uses thereof
CN122499353A